Computational science and its applications - Sreenivasan, Katepalli R.; Siddiqi, A. H.; Singh, R. C.; Gowda, G. D. Veerappa (Boca Raton : CRC Press, 2021)
Computational science is a rapidly growing multidisciplinary field concerned with the design, implementation, and use of mathematical models to analyze and solve real-world problems. It is an area of science that spans many disciplines and which involves the development of models and allows the use of computers to perform simulations or numerical analysis to understand problems that are computational and theoretical. Computational Science and its Applications provides an opportunity for readers to develop abilities to pose and solve problems that combine insights from one or more disciplines from the natural sciences with mathematical tools and computational skills. This requires a unique combination of applied and theoretical knowledge and skills. The topics covered in this edited book are applications of wavelet and fractals, modeling by partial differential equations on flat structure as well as on graphs and networks, computational linguistics, prediction of natural calamities and diseases like epilepsy seizure, heart attack, stroke, biometrics, modeling through inverse problems, interdisciplinary topics of physics, mathematics, and medical science, and modeling of terrorist attacks and human behavior. The focus of this book is not to educate computer specialists, but to provide readers with a solid understanding of basic science as well as an integrated knowledge on how to use essential methods from computational science. Features: Modeling of complex systems Cognitive computing systems for real-world problems Presentation of inverse problems in medical science and their numerical solutions Challenging research problems in many areas of computational science This book could be used as a reference book for researchers working in theoretical research as well as those who are doing modeling and simulation in such disciplines as physics, biology, geoscience, and mathematics, and those who have a background in computational science.
Chapter 1: Ingredients for applied Fourier analysis Hans G. Feichtinger Chapter 2: Industrial applications of optimal control for partial differential equations on networks: reduction and decomposition methods applied to the discrete-continuous control of gas flow in complex pipe systems Gunter Leugering Chapter 3: A model to access the role of spatial urban configurations on crowd evacuation dynamics during terrorist attacks D. Provitolo, R. Lozi and E. Tric Chapter 4: Free radical processes in medical grade UHMWPEM. Shah Jahan, Benjamin Walters, Afsana Sharmin and Saghar Gomrok Chapter 5: Computational algorithms for ill-posed inverse problemsTaufiquar Khan Chapter 6: On an efficient family of Steffensen like methods for finding nonlinear equations Vali Torkashvand and Manochehr Kazemi Chapter 7: Computational methods for conformable fractional differential equationsA. H. Siddiqi, Ram Chandra Singh and Santosh Kumar Chapter 8: Pan-sharpening using modified nonlocal means based guided image filter in NSCT domain Tarlok Singh and Pammy Manchanda Chapter 9: Moser-Trudinger and Adams inequalitiesKunnath Sandeep Chapter 10: Computational ship hydrodynamics: Modeling and Simulation Sashikumaar Ganesan, Bhanu Teja and Thivin Anandh Chapter 11: DNA-drug interaction: insight from computer simulationsAnurag Upadhyaya, Shesh Nath and Sanjay Kumar Chapter 12: A graphical user interface for palmprint recognition Rohit Khokher and Ram Chandra Singh Chapter 13: Wavelet approach for the classification of autism spectrum disorderNoore Zahra, Kahkashan Tabassum, Sahar A. El Rahman, Hussah N. Al Eisa and Mona Jamjoom Chapter 14: De-noising Raman spectra using total variation de-noising with iterative clipping algorithmPadmesh Tripathi, Nitendra Kumar and A. H. Siddiqi Chapter 15: An efficient identity based mutual authentication protocol for cloud computing Vinod Kumar and Musheer Ahmad Chapter 16: Development of statistical yield forecast model for rice using weather variables over Gorakhpur district of eastern U.P.R. Bhatla, Rachita Tulshyan, Babita Dani and A. TripathiChapter 17: Cognitive computing agent systems: an approach to build future real-world intelligent applications A. Chandiok, A. Prakash, A. H. Siddiqi and D. K. Chaturvedi Chapter 18: Controllability of quasilinear stochastic fractional dynamical systems in Hilbert spaces R. Mabel Lizzy and K. Balachandran Chapter 19: The advection-dispersion equation with zero-order production term and various seepage velocity patterns in a heterogeneous mediumAmit Kumar Pandey and Mritunjay Kumar Singh Chapter 20: On the application of genetic algorithm and support vector machine for brain tumor classification of MRI images D. Gupta and M. Ahmad Chapter 21: Proximinality and remotality in abstract spacesSangeeta and T. D. Narang Chapter 22: Conformable fractional Laguerre and Chebyshev differential equations with corresponding fractional polynomialsAjay Dixit and Amit Ujlayan Chapter 23: Computational linguistics -- inverse problems and emerging mathematical concepts Sana Arif Ansari and Masood Alam Chapter 24: Legendre wavelets method for solution of first kind Volterra problemsPooja, J. Kumar, P. Manchanda Chapter 25: Computational linguistic analysis of retail e-commerceRashmi Bharadwaj and Aashima BangiaChapter 26: Impact of data assimilation on simulation of a monsoonal heavy rainfall event over India using ARW modelling system Shilpi Kalra, Sushil Kumar, A. Routray
OCLC-licensed vendor bibliographic record.
Keywords: Computer science -- Mathematics; Science -- Mathematical models; Science -- Data processing; COMPUTERS / Computer Engineering; COMPUTERS / Computer Simulation; COMPUTERS / Data Modeling & Design